Functional porous poly(ionic liquid)s catalyst for highly integrated capture and conversion of flue gas CO2. (1st May 2023) - Guo, Xiaoxuan; Zhang, Fenglei; Muhammad, Yaseen; Cai, Zhaotian; Gao, Lijing; Wei, Ruiping; Xiao, Guomin
Graphical abstract: Highlights: A novel Ag@Co-PIN-NH2 catalyst was prepared via green ion exchange loading method. Ag@Co-PIN-NH2 exhibited high dispersed active phase and CO2 adsorption capacity. The novel catalysts showed catalytic diversity for flue gas CO2 conversion at ambient reaction conditions. Ag@Co-PIN-NH2 remained highly active for four successive reuses. Abstract: Most of the strategies developed to convert CO2 to high value-added chemicals require high purity of CO2 . To reduce the energy consumption of CO2 purification, this work reports the preparation of a poly(ionic liquid)s catalyst Ag@Co-PIN-NH2 with dual functions of adsorption and activation. The –NH2 functional group was introduced into the organic polymer framework and the Ag(I) active phase was deposited on the framework carrier through anionic exchange reaction. The highly polar surface and highly dispersed active phase of Ag@Co-PIN-NH2 facilitated the carboxylative cyclization and hydration of propargylic alcohols with exclusive chemo-selectivity under low pressure and concentration of CO2 (1 bar, 15 % CO2 in 85 % N2, v/v simulated flue gas). Furthermore, Ag@Co-PIN-NH2 exhibited broad substrate scope, excellent catalytic diversity and reusability. This work provides momentous reference information for conversion of carbon resources in industrial flue gas into valuable chemicals.